Evaluation of mechanical behaviour of the rubberized PCC mortar in fixed W/C ratio. Issue 1 (1st January 2020) - Adibi, Mahdi; Mohammadi, Mehran; Karimi, Hossein
Abstract: Addition of the waste tire rubber powder to the cement-based products is a solution for the waste problems and protecting environment. Cement-sand mortar is an integral part of masonry buildings and has an important effect on the integrity of the masonry walls. In the current research, mechanical properties and microstructures of the rubberized mortar have been investigated over various lifetimes and the cement content of the mortar was optimized by Pareto solutions. Portland composite cement (PCC) was used for making the rubberized mortar. The amount of rubber additive to the mortar specimens is considered to be 5%. The cement and water content were the variable parameters in the mixture designs while the ratio of W/C was fixed and equalled to 0.6. The microstructure analysis of the test specimens showed that the adherence of the rubber powder particles in the mortar mixture would be more effective with increasing of the cement content, and the negative effects of using rubber powder on the mortar structure can be minimized by choosing the appropriate mixture design. Also, it shows that by increasing the amount of cement in the mixture design of rubberized mortar, the compressive, tensile and flexural strengths of the mortar would be very close to the plain mortar specimens, and in some cases, the tensile and flexural strength of the mortar specimens would be increased regarding the plain mortar specimens.